On Representing Aesthetic Values of Literary Work in Literary Translation - Ma, Huijuan (Meta, 2009)
AbstractThe beauty of literary translation is determined by the artistic nature of the original work. Therefore, how to represent its aesthetic values should be considered the ultimate objective of literary translation. This paper, which is theoretically based on formal and non-formal aesthetic constituents of literature classified by the Chinese translation theorist Liu Miqing as well as traditional Chinese philology and modern literature stylistics, discusses extensively how to succeed in representing aesthetic values of literary works from two aspects, i.e., formal aesthetic markers and non-formal aesthetic markers. It also points out that since in a literary work formal markers and non-formal markers are really inseparable, the proper combination of the two can provide a satisfactory solution.